2009
DOI: 10.1038/jid.2008.442
|View full text |Cite
|
Sign up to set email alerts
|

pH-Regulated Mechanisms Account for Pigment-Type Differences in Epidermal Barrier Function

Abstract: To determine whether pigment type determines differences in epidermal function, we studied stratum corneum (SC) pH, permeability barrier homeostasis, and SC integrity in three geographically disparate populations with pigment type I–II versus IV–V skin (Fitzpatrick I–VI scale). Type IV–V subjects showed: (i) lower surface pH (≈0.5 U); (ii) enhanced SC integrity (transepidermal water loss change with sequential tape strippings); and (iii) more rapid barrier recovery than type I–II subjects. Enhanced barrier fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
177
4
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 131 publications
(193 citation statements)
references
References 47 publications
5
177
4
1
Order By: Relevance
“…In addition, patients with pigmented skin have a reduced risk for melanoma [65,66] . Recent studies have demonstrated that SC function is also influenced by pigmentation [42] . Although the present study does not show a difference in basal TEWL between vitiligo-involved and uninvolved sites, we have found that barrier recovery is significantly delayed in vitiligo-involved sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, patients with pigmented skin have a reduced risk for melanoma [65,66] . Recent studies have demonstrated that SC function is also influenced by pigmentation [42] . Although the present study does not show a difference in basal TEWL between vitiligo-involved and uninvolved sites, we have found that barrier recovery is significantly delayed in vitiligo-involved sites.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, sodium/hydrogen (Na + /H + ) exchangers, key regulators of pH [39] , are expressed on melanocytes and colocalize with melanosomes; melanosomes are also acidic [40,41] . Recent studies have demonstrated that the skin surface pH is lower in darker-than in lighter-skinned individuals [42] . Thirdly, alterations in keratinocyte proliferation have been observed in vitiligo.…”
Section: Introductionmentioning
confidence: 99%
“…While humid and dry HEEs show similar morphology at the light microscopy level, dry HEEs display a marked increase in the CD density in the SC compactum, as visualized by its ultrastructure. Since there is a direct relationship between number of CD and the strength of CC cohesion, [37][38][39] the increased CD density in dry HEEs likely reflects a more cohesive SC. It is interesting to note that the CC density in the dry HEEs approaches the density found in normal human SC (24.7% vs. *20%).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it could provide a deeper understanding of the relationship between the epidermal barrier function and skin pigmentation. 1,2 The nature and distribution of melanin in the epidermis plays an important role in determining human skin color. After being synthesized in melanocytes, melanin is transferred into neighboring keratinocytes as membrane-bound vesicles termed melanosomes.…”
Section: Introductionmentioning
confidence: 99%